2009
DOI: 10.1080/13854040902794995
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Discrepancies in Children at the Ends of the Bell Curve: A Note of Caution for Clinical Interpretation

Abstract: Discrepancies between IQ scores on the Wechsler Abbreviated Scale of Intelligence (WASI) and scores from the Delis-Kaplan Executive Function System (D-KEFS) were examined at different levels of intellectual functioning in 470 normal-functioning youths (aged 8-19) from the co-standardization sample of the WASI and D-KEFS. Results demonstrated that children with lower IQ scores often had significantly higher D-KEFS scores, whereas children with higher IQ scores often had significantly lower D-KEFS scores. Simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…It is important to note that children with ADHD in this study were tested off medication, which Jepsen and colleagues (2009) also suggest is likely to result in lower IQ scores. Furthermore, as some data suggest the relation of children’s executive function to intellectual ability may differ at the ends of the IQ distribution (Delis, 2007; McGee, 2009), the observed relation of working memory to PS and reading fluency measures may be different in children with lower levels of verbal ability. The current sample was not large enough to test for differences in this association across levels of ability.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that children with ADHD in this study were tested off medication, which Jepsen and colleagues (2009) also suggest is likely to result in lower IQ scores. Furthermore, as some data suggest the relation of children’s executive function to intellectual ability may differ at the ends of the IQ distribution (Delis, 2007; McGee, 2009), the observed relation of working memory to PS and reading fluency measures may be different in children with lower levels of verbal ability. The current sample was not large enough to test for differences in this association across levels of ability.…”
Section: Discussionmentioning
confidence: 99%
“…Given the frequency with which IQ tests are used in neuropsychological examinations, their use as ‘reference points’ for interpretation of deficient function in other neurobehavioural domains has been called into question for both adults and children. 13 Basic motor speed, however, may represent a neuropsychological function that is dissociable from other, more complex, cognitive functions. Research investigating the relationship between motor speed and higher cognitive functions has produced mixed results.…”
mentioning
confidence: 99%
“…In the same manner, Jepsen et al 28 reported that inattention, as measured on the Test of Variables of Attention, accounted for as much as 19% of the variation in Full-scale IQ (FSIQ) in children with ADHD when not taking medication. More recently, McGee et al 3 reported that children and adolescents with high IQ scores had significantly lower performance on the Delis–Kaplan Executive Function System, whereas those with low IQ scores had significantly higher Delis–Kaplan Executive Function System performance, suggesting that the relationship between IQ and executive control may be less robust at both ends of the bell curve. Among children with learning disorders (i.e.…”
mentioning
confidence: 99%
“…As neuropsychological measures are generally loosely correlated with IQ, we would not expect all these scores to be at the high level, owing to the regression-to-the-mean effect (Larrabee, 2000). The probability of obtaining an abnormal score is inversely related to intelligence (Binder et al, 2009;McGee, Delis, & Holdnack, 2009). Still others suggest that the lack of difference between samples of IG and TD children on cognitive measures is due to ceiling effects.…”
Section: Discussionmentioning
confidence: 99%